The occurence of non-obligate cave dwelling beetles (Insecta, Coleoptera) in the biospeleological provinces of Romania: A faunal and zoogeographic analysis - EUGEN NITZU (Travaux de l'Institut de Speologie Emile Racovitza, 2023)
Beside 143 specialized (obligate) and other 85 non-obligate cave dwelling species of Coleoptera (also named troglobitic species), previously inventoried by us in the Romanian fauna, in this article we present a list of 156 of non-obligate cave dwelling species which occur in different associations in the Romanian caves, for the first time grouped on biospeleological provinces and zones. In the context of the new studies which showed that the “non-obligate” cave dwelling species do not occur randomly in the caves, but having a proved selectivity for caves, this study is focused on biogeographical aspects of non-specialized cave dwelling species.